Impact of COVID-19 on Mobile Banking Adoption: Evidence from Bangladesh - Fahad Zeya (Department of Government Studies, Universitas Syiah Kuala, 2022)
Mobile banking is an example of contactless financial inclusion which comes as a blessing during the COVID-19 pandemic. The paper highlights the factors considering the adoption of mobile banking during the pandemic. The study involves demographic factors i.e. gender, occupation, and income group as well as other factors i.e. perceived ease, checklist expenditure, social protection, trust, satisfaction, and higher charge. The regression analysis has been done to observe the influence of the variables over the actual users of mobile banking in Bangladesh. COVID-19 mobile banking adoption was not influenced by demographic characteristics, as per the study's findings. Besides, higher mobile banking charges and satisfaction have a significant influence over the adoption of mobile banking during COVID-19. On the other side, perceived ease, checklist expenditure, social protection, and trust seem to have little impact on the adoption of mobile banking during COVID-19. The paper suggests that mobile banking having the features of contactless banking activity needs to be developed and made more trustworthy. Thus, the applications of mobile banking can help to accelerate the wheels of the economy despite any pandemics.